Non-linear quantile unit root test and PPP: more evidence from Africa. Issue 7 (16th April 2018) - Bahmani-Oskooee, Mohsen; Chang, Tsangyao; Elmi, Zahra (Mila); Gelan, Abera; Ranjbar, Omid
ABSTRACT: It is now a common practice to establish stationarity of the real exchange rate as a sign of purchasing power parity (PPP) hypothesis. In this article, we consider the real effective exchange rates of 29 African countries. When we apply conventional linear unit root tests, we find support for the PPP in eight countries. However, when we shift to the newly introduced non-linear quantile unit root test, support for the PPP increases to 15 countries.